Desarrollo de un modelo clínico predictivo de enfermedad hipertensiva inducida por la gestación - Pinco Cabanillas, Carlos Alberto (2018)
To develop a predictive clinical model of hypertensive disease induced by gestation. MATERIAL AND METHOD: Retrospective analytical observational study. Pregnant women from Hospital Regional Docente de Trujillo between January 2010 and June 2016 were studied. Using clinical-epidemiological and sociodemographic variables, a bivariate analysis was performed to determine the possible predictive variables of the model. Then, a logistic regression analysis was performed with progressive elimination of non-significant variables for the estimation of the best predictive model. In addition, a score was calculated by linear apposition of the risks estimated in the model. The predictive powers of the model and the score were estimated using the area under the receiver operating characteristic curve (ABC-ROC). RESULTS: 22430 pregnant women were included in the design; validation was performed by “bootstrapping” with 7343 pregnant women. In the design group, the ABC-ROC model was 0.631 and the score was 0.629. In the validation group, the ABC-ROC model was 0.616 and the score was 0.614. The p-value was <0.001 in both curves. CONCLUSION: A clinical model constructed with clinical-epidemiological and sociodemographic criteria allows predicting the hypertensive disease induced by pregnancy